Numerical investigation of combustion characteristics of extended coherent flame model 3 zones (ECFM-3Z) in diesel engines running with biodiesel - Ozbilen, Seyma Karahan; Kaleli, Emrullah Hakan; Aydar, Emir (WILEY, 2024)
This research investigates the application of Extended Coherent Flame Model-3 Zones (ECFM-3Z) to assess the performance and emissions of rapeseed oil methyl ester (ROME). Experimental tests were carried out using a Lombardini 3 LD 350 model single-cylinder diesel engine, at 1600-3000 rpm with 200 rpm speed increments, under full load conditions. For numerical analysis, STAR-CD/ESICE software was employed. Methyl Oleate (C19H36O2) was predicted as the surrogate biodiesel based on Gas Chromatography (GC) analysis and average mass calculation. Notably, the numerical analysis revealed a remarkable similarity in brake power between the experimental and computational investigations. In the range of 2400-3000 rpm, the biodiesel's performance exhibited a maximum deviation of 5%, primarily attributed to pumping, thermal, and friction losses. In terms of emissions, carbon dioxide (CO2) emissions were consistent with the findings of the experimental study, with a maximum disparity of 10%. However, carbon monoxide (CO) emissions ranged from 57% to 65% lower than those observed in the experimental study, while nitrogen oxide (NOx) emissions exhibited a reduction of 63% to 84%. In contrast, oxygen (O2) emissions were notably higher, ranging from 93% to 117% compared to the experimental study, and exhaust temperatures were elevated by 33% to 49% in comparison to the experimental results.
Keywords: 3D combustion modeling; alternative fuels; biofuels; internal combustion engines; OIL METHYL-ESTER; EMISSION CHARACTERISTICS; EXHAUST EMISSIONS; FUEL BLENDS; PERFORMANCE; JATROPHA; KARANJA; NOX; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology